Characteristics Carcass of Steer and Bull of White Brahman Crossbred Cattle at Different Ages - Sugesti, Madiyan; Susilo, Agus; Kuswati, Kuswati (Universitas Halu Oleo, 2022)
The objective of this study was to determine the effect of sex and age of slaughter on the carcass characteristics of white Brahman crossbred cattle in feedlot Lampung, Indonesia. A total of 126 white brahman cattles consisting of 63 steers (21 PI0, 21 PI1, 21 PI2) and 63 bulls (21 PI0, 21 PI1, 21 PI2) were selected for this study. The slaughter was conducted using non stunning method using box mark 4. Data analysis was done using factorial completely randomized design and Duncan's continued test. The results showed that the slaughter age factor significantly (P <0.05) had a significant effect on slaughter weight, carcass weight, carcass percentage, meat weight, fat weight, fat percentage, bone weight, bone percentage, meat bone ratio (MBR), meat fat ratio (MFR) and rib eye area (REA). The interaction of sex and slaughtering age factors showed a significant effect (P <0.05) on slaughter weight, carcass weight, meat weight, meat percentage, bone percentage, and MBR. Sex and age of slaughtering had no significant effect (P> 0.05) on the thickness of the back fat of the white Brahman crossbred cattle. It can be concluded that the factors of sex and age have an effect on the carcass characteristics of the white Brahman crossbred cattle.Keywords: Carcass Characteristics, White Brahman Crossbred, Steer, Bull, Age